2023
DOI: 10.2147/ijwh.s403347
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Anti-Müllerian Hormone, Luteinizing Hormone to Follicle-Stimulating Hormone Ratio, Testosterone, and Prolactin to Predict Polycystic Ovary Syndrome Among Sudanese Women

Abstract: Background: Polycystic ovary syndrome (PCOS) is one of the most important contributing factors to infertility. The diagnosis of PCOS is not an easy procedure, as the signs and symptoms are heterogeneous and of undefined etiology. There are only a few published studies that address the diagnostic performance of anti-Müllerian hormone in diagnosis of PCOS in sub-Saharan Africa including Sudan.Objective: This study aims to assess anti-Müllerian hormone (AMH), luteinizing to follicle-stimulating hormone ratio (LH:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Hormonal imbalances, particularly related to the hypothalamic–pituitary–ovarian axis, are a frequent underlying cause of primary amenorrhea [ 48 ]. Assessment of hormones such as follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol, and androgens can provide valuable insights into the potential endocrine disruptions contributing to the condition [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal imbalances, particularly related to the hypothalamic–pituitary–ovarian axis, are a frequent underlying cause of primary amenorrhea [ 48 ]. Assessment of hormones such as follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol, and androgens can provide valuable insights into the potential endocrine disruptions contributing to the condition [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that a small number of children had elevated adrenocorticotropic hormone (ACTH), luteinizing hormone (LH), follicle-stimulating hormone (FSH), and prolactin (PRL) hormones, which are rare in ACC. However, most were only slightly elevated and were considered to be disorders of the hypothalamic–pituitary–gonadal axis due to disturbances in sex hormone levels; they can be analogous to the polycystic ovary syndrome in women [ 15 17 ]. There were 3 cases of elevated LH, FSH, and PRL in our study, and they were all female, aged 7 months, 3 months, and 13 years old, respectively.…”
Section: Discussionmentioning
confidence: 99%